The cyclicality in SICR: Mortgage modelling under IFRS 9 - Edward Gaffney; Fergal McCann (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2019)
Banks mustmake forward-looking provisions for loan losses undernewinternational accounting standards introduced in 2018. In Europe, banks will assign performing exposures to a new "Stage 2" category with a higher provisioning penalty, if they have experienced significant increase in credit risk (SICR).We use a loan-level credit risk model and Irish residential mortgage panel data to assign performing loans into the appropriate stage. Using this technique, we characterise approximately 30 per cent of the performing Irish mortgage portfolio at end-2015 as Stage 2.We then calculate backward-looking, static estimations of Stage 2 mortgages between 2008 and 2015. This exercise suggests that loan stage assignment can be highly pro-cyclical. The share of Stage 2 among performing mortgages rises during the economic downturn to peak in 2013, after which large transitions are assigned from Stage 2 into lowerrisk performing loans, as the economy improves.
Keywords: G21; 330; mortgage defaults; credit risk; stress testing; loan provisioning